PENGARUH AGGRESSIVE INVESTMENT POLICY TERHADAP PROFITABILITAS DAN NILAI PERUSAHAAN (PERUSAHAAN JASA SEKTOR PROPERTY, REAL ESTATE DAN KONSTRUKSI SUB SEKTOR KONSTRUKSI DAN BANGUNAN) YANG TERDAFTAR DI BURSA EFEK INDONESIA (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2019)
The purpose of this research is to find the effect of Aggressive Investment Policy on profitability as measured by Return on Assets and examine the effect of Aggressive Investment Policy on firm value as measured by Tobin's q. The population in this research are nine (9) construction companies that registered on Indonesia Stock Exchange (IDX) with period 2010-2015. The result of data analysis shows that it has no effect of Aggressive Investment Policy (AIP) on profitability as measured by Return On Asset (ROA). However, it shows that Aggressive Investment Policy (AIP) has an effect on firm value as measured by Tobin's q.Keywords: Aggressive Investment Policy , Return on Asset, Tobins q